The Impact of Help-Seeking for Depression: A Mathematical Model - Aguilar Álvarez, Daniel (2022)
For years and with the Covid-19 pandemic, mental illnesses such as depression have emerged. According to the World Health Organization, an average of 5% of the population in a country suffers from depression. The investigations address this issue from cultural, economic, and social perspectives, among others, to obtain conclusions about different treatments or ways to approach a solution. We model the influence of people that sought help to treat depression on the depressive population as a {\it socially-transmitted} disease and use it to explore the effect of that population on another. Will depressed people be affected by the influence of people who sought help for depression? In addition, our model considers the possibility of falling back into depression. Our model fits the estimates and available data to run simulations. The simulations allow us to analyze different effect parameters in our model and give conclusions and recommendations on possible ways to reduce the population that becomes depressed.